Suggestions from the field for return to sports participation following anterior cruciate ligament reconstruction: Alpine skiing - Kokmeyer, D.; Wahoff, M.; Mmern, M. (Journal of Orthopaedic & Sports Physical Therapy, 2012)
Alpine skiing is a high-risk sport for injuries to the anterior cruciate ligament (ACL). While descending a hill, a skier must resist large centrifugal forces at a high velocity, while the knees are positioned in postures that place the ACL at risk of injury. Skiers who undergo ACL reconstructive surgery are prone to a high rate of reinjury to the same knee and even ACL injury in the uninjured knee. A rehabilitation program that integrates the best current evidence of ACL rehabilitation and the science of skiing is essential to a successful return to alpine skiing. Unlike rehabilitation programs developed for court or field athletes, a skiing program must place a large emphasis on slow eccentric-loading and weight-bearing (closed-chain) power and endurance. The purpose of this clinical commentary is to provide the rehabilitation specialist such a program directed toward safely returning the athlete to alpine skiing.